2022
DOI: 10.1186/s12875-022-01825-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with computer-assisted structured initial assessment facilitating patient streaming to emergency departments and primary care practices: results from a cross-sectional observational study accompanying the DEMAND intervention in Germany

Abstract: Background Patient numbers in emergency departments are on the rise. The DEMAND intervention aims to improve the efficacy of emergency services by computer-assisted structured initial assessment assigning patients to emergency departments or primary care practices. The aims of our study were to evaluate patient satisfaction with this intervention and to analyse if reduced patient satisfaction is predicted by sociodemographic data, health status or health literacy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The accompanying research to the DEMAND intervention in selected hospitals reported similar factors to be associated with satisfaction of patients. 23 Several other studies also found lower satisfaction in patients with higher age, 50 51 more severe health problems such as multimorbidity, poorly controlled diabetes or migraine-related disability, 51–54 and lower health literacy. 55–57 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The accompanying research to the DEMAND intervention in selected hospitals reported similar factors to be associated with satisfaction of patients. 23 Several other studies also found lower satisfaction in patients with higher age, 50 51 more severe health problems such as multimorbidity, poorly controlled diabetes or migraine-related disability, 51–54 and lower health literacy. 55–57 …”
Section: Discussionmentioning
confidence: 95%
“…Our study is based on study arm 1 of the DEMAND intervention, which was implemented in the telephone services of eight ASHIPs located in the German federal states of Bavaria, Brandenburg, Bremen, Hesse, North Rhine-Westphalia (represented by two ASHIPs in the regions North Rhine and Westphalia-Lippe), Schleswig-Holstein and Thuringia. Results of arm 2, the implementation of the DEMAND intervention in selected hospitals, 23 and arm 3, historical control groups for arms 1 and 2, 22 are reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%